Perancangan E-Surat Menggunakan Metodologi Pengembangan Sistem Prototype - Muhammad Dedi Irawan; Risdani Muarif (Bigint Computing Journal, 2024)
This research aims to design a web-based correspondence information system using the prototype method. The research methodology involves iterative prototype development starting with gathering user requirements followed by designing system prototypes using UML diagrams. The prototypes were evaluated by users to provide feedback for refinements in subsequent iterations. Multiple iterations were conducted until a satisfactory prototype matching the user needs was obtained. The resulting prototype covers core features like incoming and outgoing mail data collection, mail disposition, and reporting. In summary, the prototype method enabled designing a good correspondence information system that fulfills the user requirements before full system implementation.